Implementation of Smart Parking System Simulation to Conserve Land Car Parking in Atjeh Shopping Center using Unity-4 - Musliyana, Zuhar; Zikra, Alfiz; Helinda, Ayu; Maizi, Zahrul (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2015)
The difficulty of finding a place to park a vehicle has become a prominent issue in the area of Banda Aceh, especially in shopping centers are crowded like Atjeh Shopping Center. Lack of parking facilities in Atjeh shopping center, causing the transfer function of a road into a parking lot, which means reducing the effective width of the road and decrease the capacity of the road. Therefore, in this study designed a smart parking system simulation to be known the workings and functions of this system which can save a parking lot also reduce traffic congestion and is expected to be implemented in a parking lot in the basement Atjeh shopping center.Keywords: Atjeh shopping center, simulation, smart parking, unity-4.